LET’S DO IT AGAIN: A SECOND QUALITATIVE ANALYSIS OF PORTUGUESE TEACHERS' ATTITUDES TOWARDS STATISTICS - Martins, José Alexandre (2017)
We continue to believe that teachers' attitudes towards statistics can have a significant effect on their own statistical training, their way of teaching statistics, and on the future attitudes of their students. The influence of attitudes in teaching statistics in different contexts was previously studied in several researches, including some of the authors. This work is part of a broader study of Portuguese of attitudes towards statistics of Portuguese in-service teachers. Here we used a qualitative content analysis of survey responses from Portuguese 2nd cycle in-service teachers (students aged 10 or 11), focusing on 9 open-ended items from the EAEE – Escala de Actitudes hacia la Estadistica de Estrada. The EAEE survey was presented to Portuguese in-service 2nd cycle teachers and all of them were asked to complete the 9 open-ended explanations, and 132 (54% of 246) chose to do this for at least one of those 9 items, but only 41(17% of 246; 31% of 132) did it to all 9 items. The 246 in-service teachers had a mean attitude total score of 97 (SD 9.5), a median of 97, higher than the indifference/neutrality 75 (mid-point of EAEE). Now we present the qualitative content analysis of the EAEE survey open-ended answers from Portuguese in-service second cycle teachers. Among teachers’ explanations for positive attitudes in the items considered, is their need for and interest in teaching statistics, and for negative attitudes they emphasize mistrust of statistics presented on television and their manipulation. These analyses allowed us to investigate teachers’ attitudes towards statistics in order to devise a way to improve them.